The Medical Duty Officer: An Attempt to Mitigate the Ambulance At-Hospital Interval - Megan H. Halliday; Andrew J. Bouland; Benjamin J. Lawner; Angela C. Comer; Daniel C. Ramos; Mark Fletcher (Western Journal of Emergency Medicine, 2016)
Introduction: A lack of coordination between emergency medical services (EMS), emergency departments (ED) and systemwide management has contributed to extended ambulance at-hospital times at local EDs. In an effort to improve communication within the local EMS system, the Baltimore City Fire Department (BCFD) placed a medical duty officer (MDO) in the fire communications bureau. It was hypothesized that any real-time intervention suggested by the MDO would be manifested in a decrease in the EMS at-hospital time. Methods: The MDO was implemented on November 11, 2013. A senior EMS paramedic was assigned to the position and was placed in the fire communication bureau from 9 a.m. to 9 p.m., seven days a week. We defined the pre-intervention period as August 2013 - October 2013 and the post-intervention period as December 2013 - February 2014. We also compared the post-intervention period to the “seasonal match control” one year earlier to adjust for seasonal variation in EMS volume. The MDO was tasked with the prospective management of city EMS resources through intensive monitoring of unit availability and hospital ED traffic. The MDO could suggest alternative transport destinations in the event of ED crowding. We collected and analyzed data from BCFD computer-aided dispatch (CAD) system for the following: ambulance response times, ambulance at-hospital interval, hospital diversion and alert status, and “suppression wait time” (defined as the total time suppression units remained on scene until ambulance arrival). The data analysis used a pre/post intervention design to examine the MDO impact on the BCFD EMS system. Results: There were a total of 15,567 EMS calls during the pre-intervention period, 13,921 in the post-intervention period and 14,699 in the seasonal match control period one year earlier. The average at-hospital time decreased by 1.35 minutes from pre- to post-intervention periods and 4.53 minutes from the pre- to seasonal match control, representing a statistically significant decrease in this interval. There was also a statistically significant decrease in hospital alert time (approximately 1,700 hour decrease pre- to post-intervention periods) and suppression wait time (less than one minute decrease from pre- to post- and pre- to seasonal match control periods). The decrease in ambulance response time was not statistically significant. Conclusion: Proactive deployment of a designated MDO was associated with a small, contemporaneous reduction in at-hospital time within an urban EMS jurisdiction. This project emphasized the importance of better communication between EMS systems and area hospitals as well as uniform reporting of variables for future iterations of this and similar projects.